Scholarly personae in the history of Orientalism, 1870-1930 - Engberts, Christiaan; Paul, Herman (Brill, 2019)
"This volume examines how the history of the humanities might be written through the prism of scholarly personae, understood as time- and place-specific models of being a scholar. Focusing on the field of study known as Orientalism in the decades around 1900, this volume examines how Semitists, Sinologists, and Japanologists, among others, conceived of their scholarly tasks, what sort of demands these job descriptions made on the scholar in terms of habits, virtues, and skills, and how models of being an orientalist changed over time under influence of new research methods, cross-cultural encounters, and political transformations. Contributors are: Tim Barrett, Christiaan Engberts, Holger Gzella, Hans Martin Krämer, Arie L. Molendijk, Herman Paul, Pascale Rabault-Feuerhahn and Henning Trüper"--
Includes bibliographical references and index
Keywords: Konferenzschrift -- 2016 -- Leiden; Geschichte; Orientalist; Orientalismus